The structures and diffusion behaviors of point defects and their influences on the electronic properties of 2D stanene. Issue 16 (2nd February 2017) - Shen, Limeng; Lan, Mu; Zhang, Xi; Xiang, Gang
Abstract : During the synthesis of stanene monolayers, defects are inevitably present and always affect the properties. Abstract : During the synthesis of stanene monolayers, defects are inevitably present and always affect the properties. Here we used ab initio calculations to systemically investigate the structures, diffusion behaviors and related properties of several kinds of typical point defects, including the Stone–Wales (SW) defect, single vacancy (SV-1(55|66) and SV-2(3|555)) and double vacancy (DV-1(5|8|5) and DV-2(555|777)) defects. Scanning tunneling microscopy (STM) images were also simulated to help experimentalists identify these defects in stanene. The investigation of structures and diffusion behaviors of the defects revealed that SW can be easily recovered by annealing due to its low reverse barrier, both SV-1(55|66) and SV-2(3|555) are the most stable SVs, the energetically favored DV-1(5|8|5) can be formed from two SVs coalescing together, and DV-2(555|777) can arise from DV-1(5|8|5) via bond rotation by overcoming a diffusion barrier of 0.89 eV. The point defects exhibit nontrivial influences on the electronic properties of stanene: SW can open a direct gap in the energy band without harm to the high-velocity carriers, SV-1(55|66) makes stanene metallic, and SV-2(3|555), DV-1(5|8|5) and DV-2(555|777) may change stanene to an indirect or direct band gap semiconductor. Spin orbit coupling (SOC) effects have visible influences on the electronic bands, specifically the band gaps. Our theoretical results may provide valuable insights into the identification of point defects in further experiments and the understanding of their effects on the electronic properties and potential applications of stanene.